Effect of inorganic fertilizers on the development of foot rot disease of soybean caused by Sclerotium rolfsii - B. K. DUTTA, P. R. DEB and (Indian Phytopathology, 2002)
The effect of soil amendments with chemical fertilizers on the rhizosphere micro flora and on the development of foot rot disease of soybean was studied in-vivo. The fertilizers significantly increased bacteria but reduced fungi (excepting rock phosphate at 0.10 and 0.25%) and actinomycete in soybean rhizosphere. Rock phosphate (0.25%) and urea (0.5%) increased Aspergilli while Znso 4 (0.10 and 0.25%) increased Penicillia in the rhizosphere. Soil amendments initially increased Sclerotium rolfsii population in soil resulting in increased pre-ernergence seed rot. Seedlings which escaped seed rot, delayed symptom expression. Higher concentration (0.5%) of most of the fertilizers used were found to be toxic to the growth and yield of soybean. In field, urea (80 kg/ha) and Znso 4 (10 kg/ha) initially increased S. rolfsii population which decreased slightly at a later stage. A significant reduction in the disease .was recorded with all the fertilizers used, of which Znso 4 produced the best result. Urea (80 kg/ha) and ZnS0 4 (10 kg/ha) stimulated plant growth, which was reflected on the increased plant height and yield as compared to others.